2009
DOI: 10.1051/0004-6361/200912304
|View full text |Cite
|
Sign up to set email alerts
|

A systematic study of variability among OB-stars based on HIPPARCOS photometry

Abstract: Context. Variability is a key factor for understanding the nature of the most massive stars, the OB stars. Such stars lie closest to the unstable upper limit of star formation. Aims. In terms of statistics, the data from the HIPPARCOS satellite are unique because of time coverage and uniformity. They are ideal to study variability in this large, uniform sample of OB stars. Methods. We used statistical techniques to determine an independant threshold of variability corresponding to our sample of OB stars, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
0
16

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(108 citation statements)
references
References 13 publications
6
86
0
16
Order By: Relevance
“…However, when the light curve is phased to a period of 39.22 days (bottom panel), many of the outbursts are roughly aligned and binning the data traces what could be considered an 'average' outburst for this star. Lefèvre et al (2009) use Hipparcos photometry to study variability among OB stars in a study that includes HD 81654. The authors list this star as having a variable type of 'GCAS?'…”
Section: Outburstsmentioning
confidence: 99%
“…However, when the light curve is phased to a period of 39.22 days (bottom panel), many of the outbursts are roughly aligned and binning the data traces what could be considered an 'average' outburst for this star. Lefèvre et al (2009) use Hipparcos photometry to study variability among OB stars in a study that includes HD 81654. The authors list this star as having a variable type of 'GCAS?'…”
Section: Outburstsmentioning
confidence: 99%
“…Schuster & Guichard (1984) listed HD 45314 as a very variable star in multi-band photometry collected between 1980 and 1983. Based on Hipparcos photometry, Lefèvre et al (2009) classified HD 45314 as an irregular variable of early spectral type. Figure 9 displays the photometric data along with the EWs of the Hα line.…”
Section: Photometrymentioning
confidence: 99%
“…Of the five observed stars for which periods are known, three [ Lupi (pulsation periods of 0.155 days (primary) and 0.096 days (secondary); Uytterhoeven et al 2005;Telting et al 2006), 33 Eri (0.864 days;De Cat et al 2005), and HY Vel (3.102 days; Lefévre et al 2009)] were observed with subexposures of hundredths of a period. 15 CMa (0.093-0.181 days; Shobbrook et al 2006) was observed with subexposures corresponding to less than 1/80th of the longer period, but about 1/60th of the shorter period.…”
Section: Espadons and Narvalmentioning
confidence: 99%